Lactate Testing Protocol
Lactate Testing Protocol of the Canadian Rowing Federation for elite rowers: Pre- Test procedure - The training and nutritional regimens in the two days immediately prior to the tesing session can have an impact on your results. Please follow the following suggestions: 1/ Maintain a high carbohydrate diet - Try to emphasize such things as pasta, rice, bread, and potatoes in your meals. You should consume some type of carbohydrate drink (gatorade, power ade, exceed, etc.) immediately (within 30 minutes) following your workouts. Fat and protein will have no effect on lactate levels but may detract from the amount of carbs you can consume. Avoid all alcohol. 2/ Caffeine rasises both lactate and heart rate levels Do not consume caffeinated beverages in the 90 minute period before your test. If you have a morning test and need a cup of coffee make sure you are awake early enough to have it. 3/ Avoid higher intensity training strength training and categories V, IV, and III all use carbohydrates as their major fuel source. Carb depletion will result in false results. If you are training in the two days prior to testing try to do only category VI, abd technical sessions. Please use some form of carb drink during these sessions and try to keep them to 90 minutes or less. Only one training session should be done the day before the test. The Test - This is a progressive incremental submaximal test. Each stage is three minutes long wattages are increased each stage the wattages used are determined by your category and gender (i.e. lightweight or heavyweight, male or female). Lactate samples are taken from the finger tip after each stage and 3 minutes following the end of the test. All ergs should be on setting 4 for both men and women. The wattages are as follows: STAGE LW MEN LW WOMEN HW MEN HW WOMEN 1 230 170 295 190 2 270 200 330 220 3 310 230 365 250 4 350 260 400 280 Warm up - The warm up consists of 10 minutes rowing at a pre assigned wattage. You will recieve the warm up wattage for your group when you check in at the testing session. In the past the warm ups have been as follows: Lightweight Men 200 watts Lightweight Women 160 watts Heavyweight Men 260 watts Heavyweight Women 170 watts * These values are subject to change following discussion with the coaches. Stroke rate - Stroke rate is held constant through out the test and should fall between 22 and 26 strokes per minute. Test performance - Since the average watt reading is used for this test you need to be as consistant as possible during each stage. Try not to pull all out for the first few strokes and then have to row easy for the rest of the stage. Following the test there will be a thirty minute break before the start of the 20 or 30 minute test.